2011
DOI: 10.1007/s10096-011-1244-8
|View full text |Cite
|
Sign up to set email alerts
|

Reactivity of (1 → 3)-β-d-glucan assay in bacterial bloodstream infections

Abstract: To diagnose invasive fungal infections, the detection of (1 → 3)-β-d-glucan in serum has shown variable specificity, depending on the targeted population. Several circumstances for false-positive results of beta-glucan tests have been identified, among which are severe bacterial infections. In this study, we measured (1 → 3)-β-d-glucan by the Fungitell test in the serum of 62 patients (one serum sample tested per patient) for whom invasive fungal infection was not suspected: 19 control subjects and 43 patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
37
1
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 66 publications
(41 citation statements)
references
References 32 publications
2
37
1
1
Order By: Relevance
“…Only 1 of 18 (5.5%) patients with BSI caused by Gram-positive cocci and 1 of 12 (8%) patients with BSI caused by E. coli were found to be BG positive in our cohort, compared to 66% and 38%, respectively, in other studies (7,9). Note that none of the 23 patients with P. aeruginosa BSI without IFD had a positive BG result.…”
contrasting
confidence: 59%
See 1 more Smart Citation
“…Only 1 of 18 (5.5%) patients with BSI caused by Gram-positive cocci and 1 of 12 (8%) patients with BSI caused by E. coli were found to be BG positive in our cohort, compared to 66% and 38%, respectively, in other studies (7,9). Note that none of the 23 patients with P. aeruginosa BSI without IFD had a positive BG result.…”
contrasting
confidence: 59%
“…However, existing data on the frequency of false-positive BG results during BSI with the aforementioned bacteria are inconsistent (6)(7)(8)(9)(10)(11)(12). While older studies reported up to 66% (10/15) of patients with a BSI due to Grampositive cocci having more than one sample positive for BG, a more recent analysis found only one positive BG result among 70 patients with BSI and no IFD (7,12).…”
mentioning
confidence: 99%
“…2 Prediction rule for the diagnosis of invasive candidiasis (IC) in nonneutropenic adult critically ill patients with severe abdominal conditions. Each terminal node shows the probability of the predicted event intravenous immunoglobulins, albumin, coagulation factors, and plasma protein fractions [27][28][29]. In addition, Pickering et al [29] showed in a cross-contamination experiment that excess manipulation of a sample can result in its contamination with BDG.…”
Section: Discussionmentioning
confidence: 99%
“…The reason for ICU admission was medical in 18.8 % of patients, surgical in 76.1 %, and trauma in 5.1 %. The median (IQR) length of ICU and hospital stay was 15 (10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27) and 38 (24-57) days, respectively, which were significantly higher in patients with IC compared to the other two groups. ICU and hospital crude mortality rates were 26.7 and 32.4 %, respectively.…”
Section: Study Population and Salient Findingsmentioning
confidence: 95%
“…Recently, there have been changes concerning these biomarkers. It has been reported that BDG levels are elevated in bacteremia, questioning the validity of this marker for the diagnosis of invasive fungal disease (11,12). However, studies including relevant numbers of bacteremic patients are lacking.…”
mentioning
confidence: 99%